Clinical and patient‐reported outcome profile of patients with hepatitis B viral infection from the Global Liver Registry™. Issue 4 (11th January 2023) - Younossi, Zobair M.; Yu, Ming‐Lung; Yilmaz, Yusuf; Alswat, Khalid Aida; Buti, Maria; Fernandez, Marlen Ivon Castellanos; Papatheodoridis, Georgios; Hamid, Saeed S.; El‐Kassas, Mohamed; Chan, Wah Kheong; Duseja, Ajay K.; Gordon, Stuart C.; et al.
Abstract: Chronic hepatitis B (CHB) infection is one of the most common causes of cirrhosis and liver cancer worldwide. Our aim was to assess clinical and patient‐reported outcome (PRO) profile of CHB patients from different regions of the world using the Global Liver Registry. The CHB patients seen in real‐world practices are being enrolled in the Global Liver Registry. Clinical and PRO (FACIT‐F, CLDQ, WPAI) data were collected and compared to baseline data from CHB controls from clinical trials. The study included 1818 HBV subjects (48 ± 13 years, 58% male, 14% advanced fibrosis, 7% cirrhosis) from 15 countries in 6/7 Global Burden of Disease super‐regions. The rates of advanced fibrosis varied (3–24%). The lowest PRO scores across multiple domains were in HBV subjects from the Middle East/North Africa (MENA), the highest – Southeast/East and South Asia. Subjects with advanced fibrosis had PRO impairment in 3 CLDQ domains, Activity of WPAI ( p  < 0.05). HBV subjects with superimposed fatty liver had more PRO impairments. In multivariate analysis adjusted for location, predictors of PRO impairment in CHB included female sex, advanced fibrosis, and non‐hepatic comorbidities ( p  < 0.05). In comparison to Global Liver Registry patients, 242 controls from clinical trials had better PRO scores (Abdominal, Emotional, and Systemic scores of CLDQ, all domains of WPAI) ( p  < 0.05). In multivariate analysis with adjustment for location and clinicodemographic parameters, the associations of PROs with the enrollment setting (real‐life Global Liver Registry vs. clinical trials) were no longer significant (all p  > 0.10). The clinico‐demographic portrait of CHB patients varies across regions of the world and enrollment settings. Advanced fibrosis and non‐hepatic comorbidities are independently associated with PRO impairment in CHB patients.